Competitive strategy under uncertainty - Wernerfelt, Birger; Karnani, Aneel (Strategic Management Journal, 1987)
Abstract Competitive strategy under uncertainty involves a trade‐off between acting early and acting later after the uncertainty is resolved, and another trade‐off between focusing resources on one scenario and spreading resources on several scenarios, thus maintaining flexibility. This paper analyzes both these trade‐offs taking into consideration the nature of uncertainty, industry economics, intensity of competition, and the position of a firm relative to its competitors.